A methodology for porcine circovirus 2 (PCV-2) quantification based on gold nanoparticles - Basso, Caroline R. [UNESP] (2020)
The aim of the current study is to introduce a methodology aimed at producing a biosensor that uses gold nanoparticles (AuNPs) to detect porcine circovirus 2 (PCV-2). This biosensor was based on AuNPs, which were modified with self-assembled monolayers (SAMs) and antibodies. The AuNPs' surface and virus modification process applied to enable antibody binding was accompanied by localized surface plasmon resonance (LSPR), surface plasmon resonance (SPR), transmission electron microscopy (TEM), and energy-dispersive X-ray spectroscopy (EDX). Virus quantification was possible by the light absorption difference in the spectrum at concentrations of 105, 106, 107, 108, and 109 DNA copies/mL PCV-2 in relation to quantitative PCR (qPCR), with an R2 value >0.98. The visualization of colorimetric changes in the different PCV-2 concentrations was possible without the use of equipment. The biosensor production methodology presented reproducibility and specificity, as well as easy synthesis and low cost. An enhanced version of it may be used in the future to replace traditional tests such as PCR.